Expert Perspectives on Outbreak Investigation Training: A Quality Improvement Exercise - Owen Forbes; Stephanie Davis; Amalie Dyda; Alexander Rosewell; Stephanie Williams; Cameron Moffatt; Kerri Viney (University of New South Wales, 2020)
Aims: This study aimed to achieve a better understanding of factors contributing to effective training in outbreak investigation, including characteristics of effective trainees, supervisors, and training activities. Methods: We designed a semi-structured interview aimed at exploring factors in Tynjala's 3P model related to Presage (which we defined as qualities of a good FETP trainee), Process (activities that support trainees in attaining competence as outbreak investigators, including effective supervision) and Product (qualities of a good outbreak investigation and investigator). These topics were explored principally within the context of the Australian MAE Program. Deductive content analysis was conducted on interview transcripts to construct qualitative themes relating to these topics based on interview data. Results: The principal themes identified as the key components in training a competent outbreak investigator related to: personal qualities and interpersonal skills, alongside prior qualifications; elements of effective supervision including technical and soft skills, flexibility, and personal compatibility with the trainee; and activities to best support trainee development including classroom teaching in preparation for practical experience, and the ideal approach and quantity of practical exercises. Conclusions: This study identified that effective outbreak investigators possess a broad range of skills and knowledge. These span from proficiency at epidemiological tasks to interpersonal communication, underpinned by personal attributes such as perseverance and curiosity. Similarly, supervisors should ideally demonstrate passion for teaching and investment in the holistic performance and wellbeing of trainees, providing flexibility to adapt to the needs and learning styles of each trainee. Training activities should support trainees to learn theoretical content that complements practical experience, and develop mastery and confidence by having incrementally increased responsibility and independence across successive practical scenarios. These findings will be important considerations when reviewing procedures and curriculum materials for Field Epidemiology Training Programs.